Characteristics of Religious and Spiritual Beliefs of Danish Physicians: And Likelihood of Addressing Religious and Spiritual Issues with Patients - van Randwijk, Christian Balslev (Journal of religion and health, 2019)
This study investigated the association between physicians' R/S characteristics and frequency of addressing patients' R/S issues. Information was obtained through a questionnaire mailed to 1485 Danish physicians (response rate 63%) (42% female). We found significant associations between physicians' personal R/S and the frequency of addressing R/S issues. Moreover, we identified significant gender differences in most R/S characteristics. However, no differences in frequency of addressing R/S issues were identified across gender. This raises some questions regarding the effects of gender on associations between R/S characteristics and frequency of addressing R/S issues.